2014
DOI: 10.1002/pssb.201451116
|View full text |Cite
|
Sign up to set email alerts
|

EPR, optical, and dielectric spectroscopy of Er-doped cerium dioxide nanoparticles

Abstract: authoren Abstractauthoren The cerium dioxide nanoparticles doped at low level with Er ions and with grain sizes of about 22 and 300 nm were comprehensively studied using EPR, optical and microwave dielectric spectroscopy. The EPR observation of mainly cubic sites of Er3+ dopant in CeO2 reveals that vacancies are located more distant than the nearest neighbor position. This finding does not agree with recently published results based on density functional theory calculations. Time and spectral dependences of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It should be noted that the g values of rare-earth ions in CeO 2 and CaF 2 single crystals are very close to each other [41,42]. EPR measurements of rare-earth ions in CeO 2 nanoparticles also confirm this [26,[43][44][45].…”
mentioning
confidence: 71%
“…It should be noted that the g values of rare-earth ions in CeO 2 and CaF 2 single crystals are very close to each other [41,42]. EPR measurements of rare-earth ions in CeO 2 nanoparticles also confirm this [26,[43][44][45].…”
mentioning
confidence: 71%
“…38,46,47 The size of NPs was 120-140 nm in diameter, which may result in highest cellular uptake by endocytosis and inhibit elimination by the RES, as well as promoting accumulation in tumor vasculature because of the enhanced permeability and retention effect on passive tumor targeting. 48,49 The size of the PTX-loaded MPEG-b-PCL NPs@PDA was larger than that of the nonmodified PTXloaded MPEG-b-PCL NPs; this could be ascribed to the coating of PDA on PTX-loaded NPs. The PDIs of PTX-loaded NPs and PTX-loaded NPs@PDA were 0.136 and 0.121, respectively.…”
Section: Preparation and Characterization Of Npsmentioning
confidence: 98%
“…At the same time, mechanism for their cytotoxic effect is still to be understood. Recently reported study of Er 3+ doped CeO 2 nanoparticles [35] indicates the future scope for EMR of rare earth impurity doped oxide nanoparticles.…”
Section: Discussionmentioning
confidence: 98%
“…Rakhmatullin et al [35] have recently reported EMR characterization of CeO 2 : Er 3+ nanoparticles. The obtained results are compared with appropriated characteristics of the Er-doped CeO 2 single crystal and the macroscopic powder of commercial pure cerium dioxide.…”
Section: Fe 3 O 4 Nanoparticlesmentioning
confidence: 99%